Towards a Critical Theory of Adult Learning/Education: Transformational Theory and Beyond - Arthur L. Wilson; Richard C. Kiely (Adult Education Research Conference, 2002)
Given the great promise of critical theory to transform the field of adult education and its understanding of adult learning, indeed, to create, as Mezirow boldly proclaimed two decades ago, a critical theory of adult learning, where are we now?